Collected works of Ramana Maharshi / edited by Arthur Osborne - Maharshi Ramana (London, 1980)
The Thirteenth Edition has just been released.A few additions of prominent disciples have been added but most of the pages still remain Arthur Osborne's. Ramana was a silent Teacher, if there was one. It would be more appropriate to call him the Silent One, for teaching denotes duality, the teacher and taught, while Ramana was, as a devotee wrote, the Pure Non-dual Essence. His most direct and profound teaching was transmitted in silence. However, how many were there that could immediately hear or experience the unspoken, the unwritten word? Devotees and visitors asked questions and out of his boundless compassion Bhagavan answered them in his own inimitable way, as the following excerpts will show. It was in 1911 that the first westerner, Frank Humphreys, then a policeman stationed in India, discovered Sri Ramana and wrote articles about him which were first published in The International Psychic Gazette in 1913. However, Sri Ramana only became relatively well known in and out of India after 1934 when Paul Brunton, having first visited Sri Ramana in January 1931, published the book A Search in Secret India, which became very popular. Resulting visitors included Paramahansa Yogananda, Somerset Maugham (whose 1944 novel The Razor's Edge models its spiritual guru after Sri Ramana), Mercedes de Acosta, Julian P. Johnson, and Arthur Osborne. Sri Ramana's relative fame spread throughout the 1940s. However, even as his fame spread, Sri Ramana was noted for his belief in the power of silence and his relatively sparse use of speech, as well as his lack of concern for fame or criticism.His lifestyle remained that of a renunciate. This work contains almost everything written by Bhagavan Sri Ramana Maharshi. His inspired compositions, and a number of translations from ancient Advaitic texts, representing the essence of his teachings. They fall into two categories--those which exemplify the path of surrender through love and devotion to the Divine, and those which are more doctrinal. The first group includes the Five Hymns to Sri Arunachala of which the first poem, The Marital Garland Of Letters "is among the most profound and moving poems in any language" and expresses the attitude of the soul aspiring for union with God. Sri Bhagavan has affirmed that seekers who study these works are certain to attain the bliss of liberation.
Keywords: Self